Experimental study of copper nano-fluid on thermosyphons thermal performance - Jirapol Klinbun (2018)
ï¿½ 2017, Chulalongkorn University 1. All rights reserved. A new way to remove the intense heat by developing and implementing an innovative low cost compact loop thermosyphon has been widely observed. Especially, it was concluded that nano-fluids are potential heat transfer fluids to be used as working fluid in thermosyphon. Therefore, the thermophysical or transport properties of nanofluids in thermosyphon need to be discussed. In present work was to experimental study the thermal performance of thermosyphon using a copper nano-fluid as a working fluid. The experiment was performed in order to measure the temperature distribution and compare heat transfer rate of the thermosymphon with nano-fluid and with pure water. The concentration of copper nano-particle was 10, 30 and 50 ppm. The tested working temperature was 60, 70 and 80ï¿½C. Results shown that the concentration of 50 ppm of copper nano-fluid improved thermal performance compared with the case of pure water. The optimum and behavior of copper nano-fluid in thermosyphon is presented, which highlights all of the beforehand mentioned advantages.